Prostatic calculi cause osteoblastic immunophenotype of prostate cancer - A. M. Piddubnyi; S. M. Danylchenko; A. M. Romaniuk; R. A. Moskalenko (Zaporozhye State Medical University, 2019)
Prostate cancer (PGC) is leading the way in the structure of cancer morbidity around the world. The presence of prostatic concretions (PC) and skeletal metastases significantly reduces the patients' life quality and worsens the prognosis of the disease. Aim. The aim of study was to define the impact of PC on the development of prostate cancer bone metastases. Materials and methods. 30 samples of PGC with PC and 30 PGC tissue samples without PC were analyzed by histology (hematoxylin-eosin staining), histochemistry (von Kossa and Alizarin red staining), immunohistochemistry (OSN, Col I, Col II, p53, Bax, Casp3, MPO, CD68). PC were analyzed by SEM-EDS and XRD with different temperature of heat pretreatment. Results. All PC samples had the calcium hydroxyapatite origin with a slight deviation from the stoichiometric composition and admixture of extraneous elements. The presence of zinc oxide and iron-containing calcium phosphate in the structure of PC was found by XRD. We revealed significantly higher expression of Вах, Саsp3, MPO and CD68 in PGC tissue with PC (P < 0.001). We suggest that the combination of these factors predetermines the development of a specific phenotype of cancer cells which is manifested by the significantly higher OSN and Col I expression in PGC with PC (P < 0.001). It contributes to recognizing of bone tissue as an optimal environment for the growth and development of PGC metastases by cancer cells. Conclusions. The presence of PC in the PGC tissue promotes the development of a specific osteoblastic immunophenotype of cancer cells. It can determine the tropism of PGC metastases to bone tissue.